Effect of PI3K/AKT/mTOR Signaling Pathway on Regulating and Controlling the Anti-Invasion and Metastasis of Hepatoma Cells by Bufalin - Sheng, Xia; Zhu, Pengfei; Zhao, Yi; Zhang, Jinwei; Li, Haijia; Zhao, Huan; Qin, Jianmin (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: Autophagy plays a “double-edged sword” in the process of tumorigenesis, development and metastasis. Objective: In this study, we explored the effect of PI3K/AKT/mTOR autophagy-related signaling pathway on regulating and controlling the invasion and metastasis of liver cancer cells by Bufalin. Methods: The cell counting, migration, adhesion and invasion assay were used to evaluate the effect of Bufalin on cell proliferation, invasion and metastasis. The protein expression of PI3K/AKT/ mTOR signaling pathway were detected by the Western Blotting technique. Results: After inhibiting autophagy of HCC-LM3 cells, the inhibitory effect of Bufalin on adhesion, migration and invasion of HCC-LM3 cells was significantly enhanced. Synergistic inhibition was strongest when different autophagy inhibitors were combined with 3MA and CQ. After inhibiting autophagy, Bufalin significantly inhibited the protein expression of P-AKT, Cyclin D1, MMP- 2, MMP-9 and VEGF in HCC-LM3 cells. The protein expression of PTEN and E-Cadherin in HCC-LM3 cells was significantly increased. Conclusion: The present study shows that the anti-tumor effect of Bufalin mainly inhibit proliferation, extracellular matrix degradation and angiogenesis of HCC by influencing autophagy. These findings confirm the capability of Bufalin in inhibiting metastasis of HCC and in parallel to current patents, could be applied as a novel therapeutic strategy in the prevention of metastasis of HCC.
Keywords: Autophagy